Spectrums and Prognosis of Kidney Disease in Patients with Ankylosing Spondylitis - Dafeng He; Rong Wang; Shaoshan Liang; Dandan Liang; Feng Xu; Caihong Zeng; Zheng Tang (Karger Publishers, 2020)
Background/Aims: Renal involvement was a common extra-articular manifestation of ankylosing spondylitis (AS). Few reports have investigated the pathological characteristics and renal outcomes of AS patients with kidney disease. The aim of this study was to investigate the pathological spectrums and the renal prognosis of AS patients with kidney disease. Methods: This retrospective and observational study was conducted working on 62 patients (47 males and 15 females) with a diagnosis of AS (ACR, 1984) and renal biopsies between 2008 and 2017. The histopathological findings and associated clinical manifestations were collected, and the renal prognoses of patients with kidney disease were evaluated too. Multivariate binary logistic regression analysis was performed to identify risk factors for the occurrence of IgA nephropathy (IgAN). Results: Renal biopsy revealed that IgAN accounted for a majority (74.2%) of the kidney disease with AS, while membranous nephropathies, minimal change disease, focal segmental glomerulosclerosis, and other lesions accounted for a small minority. Multivariate analysis revealed that serum immunoglobulin A >3.45 g/L and immunoglobulin G >9.06 g/L were risk factors for the occurrence of IgAN. With a median follow-up time of 24.3 months, 28 patients (50.9%) reached complete remission, 9 patients (16.4%) had partial remission, and 1 patient had an eGFR decline >30%. No difference was found in prognosis between IgAN and non-IgAN. Conclusion: IgAN occurred in 76.4% of the kidney disease with AS, and higher serum immunoglobulin A and G increased the risk for the occurrence of IgAN. The renal prognosis of kidney disease in AS was good.